A Case Study on Fish Gelatin/Microcrystalline Cellulose Biomaterial Inks for Extrusion-Based Bioprinting - Yubo Tao; Jinbao Du; Tong Hu; Peng Li; Ling Pan; Fangong Kong; Jingfa Zhang (Gels, 2025)
The development of printable, biocompatible, biodegradable, and cost-effective bioinks, or biomaterial inks, remains a focal point in extrusion-based bioprinting research. In this study, fish gelatin (FG) was reinforced with microcrystalline cellulose (MCC) to formulate biomaterial inks. These FG/MCC composite inks were fabricated into 3D scaffolds using an extrusion bioprinter. The influence of MCC concentration on printability was systematically evaluated. Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analyses confirmed the formation of hydrogen bonds between MCC and FG, indicating molecular-level interactions. Notably, MCC incorporation enhanced the rheological properties of the ink and significantly improved the compressive strength of printed scaffolds. Furthermore, MCC content modulated key scaffold characteristics, including porosity, degradation rate, swelling behavior, and microarchitecture. These findings demonstrate that FG/MCC composite hydrogels exhibit optimal properties for extrusion-based 3D bioprinting, offering a promising platform for tissue engineering applications.